Amendments to Interpretations of SAAF Inclinometer Data from the Furggwanghorn Rock Glacier, Turtmann Valley, Switzerland: Results from 2010 to 2012. Issue 4 (28th March 2016) - Buchli, Thomas; Laue, Jan; Springman, Sarah M.
Abstract : Core Ideas: Raw data from an SAAF inclinometer were processed using proprietary software. Results differed significantly from values derived using the previous software version. Direct connection between creep velocity and air and soil temperature can no longer be proposed for this specific rock glacier. Raw data processing from a ShapeAccelArray field (SAAF) inclinometer were made using proprietary software from Measurand, the manufacturer of the SAAF inclinometer. When the inclinometer data obtained from the same borehole were reprocessed with an updated software version, the results were found to differ significantly from the values derived using the previous version of software. Neither the absolute displacements, nor the curve representing displacements with depth, agreed with the previous values, despite best attempts to compare data with alternative sparse field measurements of surface displacements. There was a change in inclination of the segments above the shear zone, and the strain rates in the shear zone were reduced significantly during the winter months. In contrast, there was no change in the depth of the shear zone. Therefore, the ground model presented in the original study is still considered to be the optimal ground model of the Furggwanghorn rock glacier. Finally, a simple trigonometrical approach was conducted to investigate the validity of both software versions. The simplified recalculations could confirm mostly the results of the updated software version.